Projeção climática da frequência de eventos de precipitação intensa no Nordeste do Brasil: resultados preliminares - Andrade, Matheus de Mendonça (2013)
The frequency of Heavy Rainfall Events (HRE) in two sub-regions, north and south of Northeast Brazil (NEB) from the Eta model are investigated. It was observed that the sub-region north has, on average, higher incidence of HRE and southern sub-region has less variability. Years of extreme precipitation (many or few) were related to El Niño years. There was no strict relationship between La Niña years and years with higher frequencies of HRE. Comparing the results of the observed data of HRE with the Eta model simulations were more reliable monthly distributions with respect to annual. Predictions for the future of Eta model in north of Northeast Brazil, showed a tendency to increase the frequency of HRE and in south of Northeast, greater instability in frequency.